The Effects of In Vitro Incubation of Asthenoteratozoospermic Semen after Density Gradient Centrifugation at Room Temperature and 37oC on Sperm Parameters, Chromatin Quality and DNA Fragmentation in a Short Time Period - M Karimi Zarchi; B Maleki; M Dehghani Ashkezari; L Motamed Zadeh; A Agha-Rahimi (JRI, 2020)
Background: Sperm quality is an important factor in assisted reproductive technology (ART) that affects the success rate of infertile couples treatment. In vitro incubation of sperm can influence its parameters and DNA integrity. The present study focused on the effect of different incubation temperatures sperm parameters on asthenoteratozoospermia semen prepared with density gradient centrifugation at different times. Methods: Twenty-seven samples were collected and prepared. Then, the suspension was divided into two parts. One part was incubated at room temperature (RT), and another was incubated at 37oC. Immediately and after 2 hr (2H) and 4 hr (4H), spermatozoa were evaluated regarding motility, viability, morphology, sperm protamine deficiency, chromatin and DNA fragmentation. Statistical analysis was performed using paired t-test and repeated measures. The p<0.05 was considered statistically significant. Results: Our results showed that following 2 and 4 hr of incubation at RT, sperm progressive motility and viability decreased significantly. Sperm DNA fragmentation increased significantly following 2 and 4 hr of incubation at RT and 37oC. The Trend analysis confirmed that there were no significant differences between sperm parameters and DNA fragmentation after different times at RT and 37oC. Conclusion: Incubation of sperm at RT in comparison to 37oC didn’t preserve sperm parameters and DNA efficiently. Therefore, IVF, ICSI and IUI procedure should be performed in the soonest possible time after sperm preparation.